Tillage depth dynamic monitoring and precise control system - Kai Hu; Wenyi Zhang; Bing Qi; Yao Ji (Measurement + Control)
The tillage depth (TD) serves as a pivotal criterion for assessing the operational excellence of rotary tillers, yet the current TD control methods are plagued by a myriad of issues including subpar precision and sluggish responsiveness. The present study aimed to develop a high-precision TD monitoring model that incorporates the tilting attitude of the tractor, and investigate the impact of tractor attitude inclination and lifting hydraulic cylinder stroke on TD. The TD stability control system based on electro-hydraulic control was developed, and the model identification method was adopted to derive the accurate control function. The fuzzy adaptive PID (FAPID) method was adopted to effectively improve the response speed and resisting disturbance capacity of the electro-hydraulic system. Then the co-simulation model of the electro-hydraulic control system was constructed. Under the excitation of step and sine functions, the FAPID control algorithm can reduce the rise time by more than 50%, and the displacement tracking error is also effectively reduced. To verify its effectiveness, the experimental platform was constructed, and then field test trials of TD were conducted. The test results indicate that, under various operational conditions, the developed TD control device can effectively reduce the standard deviation of TD by 0.302–0.464 and decrease the variation coefficient of TD by 2.47%–2.92%. The online monitoring and precise control device of TD investigated in this paper can effectively improve the quality of tillage machinery.